Parent–infant closeness after preterm birth and depressive symptoms: A longitudinal study - Lehtonen, Liisa; Lilliesköld, Siri; De Coen, Kris; Toome, Liis; Gimeno, Ana; Caballero, Sylvia; Tameliene, Rasa; Laroche, Sabine; Retpap, Jana; Grundt, Hege; Van Hoestenberghe, Marie-Rose; Skene, Caryl; et al. (Frontiers in Psychology, 2022)
Background Preterm birth increases the risk for postpartum depression in both mothers and fathers, calling for strategies to alleviate and prevent depressive symptoms in parents of preterm infants. The aim of this study was to assess the association between early parent-infant closeness and later depressive symptoms among parents of preterm infants. We hypothesized that longer duration of closeness associate with fewer depressive symptoms in both parents. Methods This prospective cohort study included 23 neonatal intensive care units from 15 countries in 2018–2020. Each unit recruited 30 families with preterm infants. The total duration of parents’ presence in the NICU, and separately parent-infant skin-to-skin contact and holding, were measured using a Closeness Diary up to 14 days. The Edinburgh Postnatal Depression Scale (EPDS) was used at discharge and at 4 months corrected age of the infant. Results The median presence was 469 minutes (Q1 258, Q3 1087) per 24 hours for the mothers and 259 minutes (Q1 100, Q3 540) for the fathers; mean EPDS scores were 9.2 (SD 5.0) and 6.3 (SD 4.4) at discharge and 6.6 (4.7) and 4.3 (4.2) at four months, respectively. Parents’ presence and depressive symptoms varied greatly between the units. Parents’ presence as the total measure, or skin-to-skin contact and holding separately, did not associate with depressive symptoms in either mothers or fathers at either time point (adjusted). Conclusions No association was found between the duration of parent-infant closeness in the neonatal unit and parents’ depressive symptoms. The beneficial effects of family-centered care on parents’ depression seem to be mediated by other elements than parent-infant physical closeness. More research is needed to identify the critical elements which are needed to alleviate parents’ depression after NICU stay.